Adoption Status and Factors Determining Coffee Technology Adoption in Jimma Zone, South West Ethiopia. - Meskerem Million; Mezigeb Like; Tamiru Chalchisa (Indonesian Coffee and Cocoa Research Institute, 2020)
Jimma zone is one of the most potential coffee producing areas in Ethiopia. The livelihood of the farmers is mainly depend on coffee production. However,majority of them are smalholders characterized by traditional farm management system and limited use of coffee production technology. The aim of this study was to assess the adoption status of different coffee technologies in Jimma zone and to identify the determining factors of coffee technology adoption in the area. In the study, 393 respondents were involved and the adoption status of six selected coffee technologies, namely: the adoption of improved coffee variety, stumping, pruning, fertilizer, shade and mulching was investigated. Accordingly 67.4 % of the sample respondents did not use improved coffee variety. Similarly 45.8%, 31%, 53.4%, 4.1% and 25.7% of the farmers have not yet started to use stumping, pruning, fertilizer, shade tree and mulching, respectively. The factors influencing the adoption of each of these technologies were analyzed by using binomial regression model. As a result, age was found to be significant and negatively correlated with adoption of improved coffee variety. Sex of the farmer was the second variable which was found to be significant and had a negative correlation with mulching practice. Educational status was the other important factor which was found to be significant and had a positive correlation with adoption of the improved coffee variety, stumping technology and using shade tree. Family size was also found to be significant and had a positive correlation with using of stumping technologies, pruning, fertilizer application, mulching and shade trees. Dependency ratio, which was significant and showed a negative correlation with stumping and fertilizer application, was found to have a positive correlation with pruning. Likewise coffee farm size was found to be significant and had a negative correlation with improved coffee variety, fertilizer and mulching but it had a positive significant correlation with stumping. The coffee growing experience of the farmers was also significant and had a negative correlation with stumping, pruning and fertilizer. Moreover development agent support had a significant positive correlation with adoption of improved coffee variety, stumping, pruning, fertilizer application and mulching.Market distance was a factor that had a negative correlation with adoption of improved coffee variety, stumping, shade and mulching. Cooperative membership also showed a significant and negative corelation with improved coffee variety and pruning. Credit on the other hand was found to have a positive correlation with fertilizer application and was negatively correlated with the adoption of pruning practice and mulching. The total income of the household was found to be significant and had a positive correlation with adoption of improved coffee variety, pruning, using fertilizer and using of shade tree and training was also found to have a positive relationship with adoption of improved coffee variety, stumping technology, pruning practice, using shade tree and mulching.